Analisis Pengaruh Rasio BOPO, EPS, LDR, NPL dan ROE Terhadap Fluktuasi Harga Saham Pada Bank Bumn Besar - Joshua, Michael Balli; Sibarani , Mentiana (Green Publisher Indonesia, 2025)
This study aims to analyze the influence of BOPO, EPS, LDR, NPL, and ROE ratios on the stock prices of major state-owned banks in Indonesia. The background highlights the strategic role of state-owned banks in supporting national economic stability, along with the stock price fluctuations that occurred in 2024 on the Indonesia Stock Exchange, posing challenges for investors. The research applies a quantitative approach using multiple linear regression analysis to examine the effect of financial ratios on stock prices. The data used consists of quarterly financial reports of BNI, BRI, and Bank Mandiri for the period from 2020 to 2024. Analytical techniques include classical assumption tests, regression analysis, F and t tests, and the coefficient of determination. The results reveal that, simultaneously, BOPO, EPS, LDR, NPL, and ROE significantly affect the stock prices of major state-owned banks, with an R² value of 0.961. Partially, BOPO and NPL have a significant negative impact on stock prices, while EPS, LDR, and ROE exert a significant positive influence. These findings underscore the importance for bank management to effectively manage these financial ratios to improve stock value, attract investors, and contribute positively to the stability and growth of Indonesia’s capital market.